The value of Cystatin C in the diagnosis of cardiorenal syndrome type 1. (14th October 2021) - Phan, H A O
Abstract: Background: The presence of acute kidney injury in the setting of acute heart failure is very common occurrence and was termed cardiorenal syndrome 1 (CRS1). In CRS1 the diagnosis of acute kidney damage is often delayed by creatinine and urine output following KDIGO standards (Kidney Disease Improving Global Outcomes). Cystatin C is one of the earliest markers of worsening renal function. We studied the value of plasma Cystatin C in the diagnosis of cardiorenal syndrome type 1. Purpose: This study was aimed: (1) to decribe clinical, subclinical characteristics, prevalence of CRS1; (2) to evaluate the diagnostic efficacy of Cystatin C in diagnosis of CRS1. Materials and method: There were 139 patients with acute heart failure or acute decompensated heart failure (ADHF) in the Department of cardiovascular resuscitation and Interventional cardiology at 115 Ho Chi Minh City People's Hospital from September 2018 to June 2019. This is a prospective cohort study. Results: There were 48 cases (rate 34.5%) with CRS1, medium age 66.12±15.77, men accounted for 50.4%. The optimal cut-off Cystatin C for diagnosing CRS1 is >1.81 mg/dl, AUC is 0.787 (95% CI 0.71–0.85, p<0.001), sensitivity 75%, specificity 83.52%, positive predictive value 70.6%, negative predictive value 86.4%. Building the optimal regression model by the BMA (Bayesian Model Average) method with only one variable Cystatin C: Odds Ratio = e y, while y = −2.75 + 1.11x Cystatin C. Moreover, a nomogram with variable Cystatin C was designed to predict the likelihood of CRS1 with AUC 0.842. Ultimately, a confusion matrix was constructed to determine model accuracy 81.82%, sensitivity 78.26%, specificity 100%, positive predictive value 100%, negative predictive value 47.37%. Conclusions: Cystatin C is quite good value in the diagnosis of CRS1 in patients with acute heart failure or ADHF. A predictive model based on Cystatin C may help early diagnose CRS1 in patients with acute heart failure or ADHF. Funding Acknowledgement: Type of funding sources: None.